Endoprosthetic Reconstruction for a Displaced Atypical Femoral Fracture in a Cancer Patient with Poor Prognosis - Hironari Tamiya; Hiroki Hagizawa; Takaaki Nakai; Yoshinori Imura; Takaaki Tanaka; Kazuya Oshima; Toshikazu Ito; Norifumi Naka; Shigeyuki Kuratsu (Case Reports in Orthopedics)
Zoledronate or denosumab treatment is beneficial for cancer patients with bone metastasis. However, each agent may trigger atypical femoral fractures. Incomplete atypical femoral fractures can be successfully treated with prophylactic intramedullary nailing. On the other hand, intramedullary nailing for displaced atypical femoral fractures occasionally causes problems with regard to bone healing, resulting in long-term treatment. In cancer patients with poor prognosis who experience atypical femoral fractures, improvement in activities of daily living should be the priority. Thus, we performed endoprosthetic reconstruction for a displaced atypical femoral fracture in a breast cancer patient with poor prognosis to enable walking in the early stage after the operation. Two weeks after the operation, she could successfully walk. The postoperative Musculoskeletal Tumor Society score was 47%, and it had improved to almost the preoperative level before injury (50%). In conclusion, endoprosthetic reconstruction for displaced atypical femoral fractures may be a first-line treatment approach to acquire early postoperative walking ability for improving activities of daily living in cancer patients with poor prognosis.